NILAI-NILAI BUDAYA DALAM CERITA RAKYAT ASAL-USUL PAYANDERKET KAB KARO - Sembiring, Lija Melisa Br (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This study aims to determine the cultural values contained in the folklore of the origin of the Karo district Payanderket. Cultural values are contained in the contents of the Payanderket story and supporting theories. This research uses descriptive analysis method. Some steps taken to obtain and analyze this research are conducting interviews with sources, classifying sources obtained from the folklore of the origins of Payanderket and then applied in writing, then reviewed to determine the cultural value contained therein, to conclude the results of research . The data obtained is referred from various library sources and then grouped based on certain criteria. The results showed that there were five cultural values namely, kinship values, religious values, legal values, conflict values, and compassion values. Each value has a very deep meaning showing the authenticity of the folklore of the origin of the Karo Regency Payanderket. By understanding and understanding the contents of the folklore of the origins of the Karo district Payanderket, it will be easier to obtain wisdom and learning the value of life from the folklore of the origin of the Payanderket Karo district.